Implementasi Kebijakan Penggunaan Qris Terhadap Praktik Umkm Sebagai Upaya Percepatan Pertumbuhan Ekonomi Digital - Utomo, Satrio; Safuan, Safuan; Alkadhim Alhabsy, Musa (Fakultas Ekonomi Universitas Gresik, 2023)
UMKM activities are a very strategic practice to encourage people to use the digital economy, but this cannot be implemented properly because it still requires the use and understanding of technology, then regulations are also needed that can reach the problems of the smallest UMKM sector, where the existing PADG must equipped and even refurbished. The implementation of QRIS based on existing regulations through PADG is not optimal and comprehensive, so further regulations are needed to regulate digital economic innovation issues that can reach QRIS users down to even the smallest sectors, such as PBI. Thus, UMKM can play a role in encouraging the development of the digital economy in Indonesia